Application of wavelets transform for analysis of images of gas-discharge radiation of water - Glukhova, N. V.; Pesotskaya, L. A.; Kuchuk, N. G.; Kharlamova, J. N. (Харківський університет Повітряних Сил ім. Івана Кожедуба, 2016)
The issues of experimental methods of studying biological water properties are considered. The existing problems of theoretical and experimental studies of water properties are described, the key value of features of the structure of water for normal functioning of living organisms is shown. Since the standard classical methods of physical and chemical analysis do not provide the possibility of implementing experimental evaluation of specific biological properties of water, as an alternative, there is proposed a method of recording gas discharge irradiance of liquidphase objects in an electromagnetic field followed by software image processing based on wavelet analysis. The efficiency of the proposed method was tested on real data samples for distilled water samples and natural water. The results obtained from the extraction of specific parameters of structural features of gas discharge radiance images demonstrate the effectiveness of wavelet analysis algorithms for images of radiation of water samples with different biological properties.

Робота присвячена питанням експериментальних методів дослідження біологічних властивостей води. Розглянуто існуючі проблеми теоретичного та експериментального дослідження властивостей води, показано ключове значення особливостей структури води для нормального функціонування живих істот. Оскільки класичні методи фізикохімічного аналізу не забезпечують можливості реалізації експериментальної оцінки специфічних біологічних властивостей води, то, у якості альтернативного способу, запропонований метод реєстрації зображень газорозрядного випромінювання рідиннофазних об’єктів в електромагнітному полі з подальшою програмною обробкою зображень на основі вейвлет-аналіза. Ефективність запропонованого методу апробовано на реальних вибірках даних для зразків дистильованої, водопровідної та природної води. Отримані результати вилучення специфічних параметрів зі структурних особливостей зображень газорозрядного випромінювання демонструють ефективність алгоритмів вейвлет-аналізу зображень випромінювання зразків води з різними біологічними властивостями.
Використання вейвлет-перетворення для аналізу зображень газорозрядного випромінювання зразків води
Keywords: gas discharge radiation; digital image processing; wavelet analysis; біологічні властивості води; цифрова обробка зображень; електромагнітне поле